Expression and meaning: Studies in the theory of spech arts - Searle, John R. (Cambridge Cambridge University Press, 1979)
John Searle's Speech Acts made a highly original contribution to work in the philosophy of language. Expression and Meaning is a direct successor, concerned to develop and refine the account presented in Searle's earlier work, and to extend its application to other modes of discourse such as metaphor, fiction, reference, and indirect speech arts. Searle also presents a rational taxonomy of types of speech acts and explores the relation between the meanings of sentences and the contexts of their utterance. The book points forward to a larger theme implicit in these problems - the basis certain features of speech have in the intentionality of mind, and even more generally, the relation of the philosophy of language to the philosophy of mind.